Exploring the nature of weak Chandra sources near the Galactic Centre - Bandyopadhyay, R; Miller-Jones, J; Blundell, K; Bauer, F; Podsiadlowski, P; Wang, Q; Rappaport, S; Pfahl, E (American Institute of Physics, 2005)
We present results from the first near‐IR imaging of the weak X‐ray sources discovered in the Chandra/ACIS‐I survey (Wang et al. 2002) towards the Galactic Centre (GC). These ∼800 discrete sources, which contribute significantly to the GC X‐ray emission, represent an important and previously unknown population within the Galaxy. From our VLT observations we will identify likely IR counterparts to a sample of the hardest sources, which are most likely X‐ray binaries. With these data we can place constraints on the nature of the discrete weak X‐ray source population of the GC.